Monetary Public Levies in Poland and Ukraine: the Comparative Analysis: Introduction, Public levies in the Polish and Ukrainian Constitutions, Public tributes in legal literature, Conclusion - KORNIEIEV, PETRO; BRZEZICKI, TOMASZ (PRAWO i WIĘŹ, 2024)
The aim of this paper is a comparative analysis of the legal regulations that established public tributes in Poland and Ukraine, the doctrine of tax and public law, and an attempt to define the concept of public tributes. This study aimed to examine the legislator’s approach, in particular on the grounds of the Constitution, to the issue related to public tributes. Determining the difficulties and growth of public levies in Poland and Ukraine was especially crucial. The analyses conducted for this study should support the idea that a systemic definition of public tributes is needed.